The Effects of Peer Feedback on EFL Students’ Writing Performance (Journal of Contemporary Educational Policies and Practices, 2022)
Nowadays, the common problem confronting English as a foreign language (EFL) teacher in public schools is over-sized classes. This study investigates the utilization of peer feedback which is believed to reduce the teacher’s workload and increase students’ capability in learning a foreign language. The study recruited 84 EFL students who learn General Business English to be the participants, of whom 42 were in the control group and the rest in the experimental group. They were asked to write a business email after a period of instructions. The participants benefiting from peer feedback outperformed those who received conventional method although both groups had an overall higher mean score in the post-test. Most of the responses to the questions in the questionnaire reached high scales of the five-point Likert scale which showed that the experimental students appreciated peer feedback provided. Some recommendations and limitations are included in the paper for future exploration.
Keywords: Classroom teacher; EFL students; peer feedback; business emails